Nickel-zinc ferrite material as well as preparation method and application thereof

By adjusting the composition and process of nickel-zinc ferrite materials, high-frequency, low-power and high Tc nickel-zinc ferrite materials are prepared, which solves the problem of high power consumption of existing materials under high-frequency conditions and improves the application and performance of the products.

CN119504247APending Publication Date: 2025-02-25HENGDIAN GRP DMEGC MAGNETICS CO LTD +1

Patent Information

Application Number
CN202311056918.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing soft magnetic nickel-zinc ferrite materials consume high power under high frequency conditions, making it difficult to meet the needs of high-performance devices such as smart wearable devices.

Method used

By adjusting the content range of Fe2O3, NiO, ZnO and CuO, and adding auxiliary components such as Bi2O3, MgO and nano SiO2, using specific ball milling, pre-firing, granulation and sintering processes, nickel-zinc ferrite materials with high frequency, low power consumption and high Tc were prepared.

Benefits of technology

It realizes high-frequency and low-power performance at frequencies of 4MHz to 14MHz, improves the application of common mode inductors, pulse transformers and stacked magnetic beads/inductors, and is suitable for avionics, automotive electronics and communication electronics fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004406294360000221
    Figure BDA0004406294360000221
  • Figure BDA0004406294360000231
    Figure BDA0004406294360000231
Patent Text Reader

Abstract

The invention provides a nickel-zinc ferrite material as well as a preparation method and application thereof. The nickel-zinc ferrite material comprises main components and auxiliary components, the main components comprise 65.8 to 67.8 wt% of Fe2O3, 6.8 to 7.5 wt% of NiO, 16.5 to 17 wt% of ZnO and 6.2 to 8.5 wt% of CuO, and the auxiliary components comprise Bi2O3, MgO and nano SiO2, and the main components comprise the following components in percentage by mass: 65.8 to 67.8 wt% of Fe2O3, 6.8 to 7.5 wt% of NiO, 16.5 to 17 wt% of ZnO and 6.2 to 8.5 wt% of CuO. The nickel-zinc ferrite material has the excellent performance of high frequency, low power consumption and high Tc, the problem of high loss of the nickel-zinc ferrite material under the high-frequency condition is solved, the output stability applicability of the inductor at the high frequency is improved, and the nickel-zinc ferrite material can be applied to the fields of avionics, automotive electronics and communication electronics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft ferrites and relates to a nickel-zinc ferrite material and a preparation method and application thereof. Background Art

[0002] Soft ferrites are mainly divided into power ferrites and high permeability ferrites according to the application type. Compared with nickel-zinc ferrites, nickel-zinc ferrites have the advantages of high resistivity and high operating frequency, and are suitable for making various types of surface mount components.

[0003] In recent years, with the continuous emergence of smart wearable devices, higher requirements have been put forward for the intelligence and miniaturization of devices. Products must be suitable for surface mounting, easy welding, high strength and other requirements, and more stringent requirements have been put forward for the high performance and reliability of devices. With the wide application of ferrite in various industries such as communications, IT industry, automobile industry, aerospace field, ships and national defense weapon equipment systems, surface mount components must meet the conditions of being suitable for surface mounting and welding, good strength and so on. The miniaturization of electronic products requires the switching power supply to be small in size, light in weight and high in reliability. The smaller the size and weight of the core of the transformer, the better. According to the working principle of the transformer, the output voltage is proportional to the frequency, that is: Vm = kfNABm, where k is the waveform factor, Bm is the working magnetic induction intensity, f is the operating frequency, A is the cross-sectional area of ​​the core, and N is the number of winding turns. Therefore, to reduce the size and weight of the transformer, it is necessary to increase the operating frequency of the switching power supply, which requires the soft ferrite material used in the switching power supply to have the characteristics of high frequency and low power consumption.

[0004] The currently used soft magnetic nickel-zinc ferrite material has a high frequency and low power consumption (at a frequency of 13.56MHz), and the power consumption is generally above 2000. The high-frequency magnetic core generally uses hexagonal Co2Y ferrite material, but the inductor made from it will have low inductance and direct cracking due to tin immersion. Therefore, the products made of this material will have disadvantages such as low energy conversion efficiency and limited operating temperature during use.

[0005] CN115448713A discloses a nickel-zinc ferrite material with high frequency, low loss and high saturation magnetic flux density. The raw material of the blank includes a main material formula and a doping formula. The main material formula is composed of Fe2O3, NiO and ZnO, and in terms of molar percentage, the content of Fe2O3 is 55.65-56.66%, the content of NiO is 20.8-23.3%, and the content of ZnO is 21.04-23%; the doping formula includes Co2O3, which accounts for 0.9-1.05% of the mass of the main material formula, MnCO3, which accounts for 2.8-2.95%, V2O5, which accounts for 0.06-0.08% and SiO2, which accounts for 0.06-0.08% of the mass of the main material formula. Compared with the existing similar materials, the nickel-zinc ferrite material prepared by using the blank meeting the above conditions has significantly improved magnetic permeability μi, Q value of the corresponding frequency, saturation magnetic flux density Bs value, etc. The invention can provide a nickel-zinc ferrite material with high magnetic permeability, high saturation magnetic flux density, high-frequency Q value and low hysteresis loss, but does not mention the performance at high frequencies.

[0006] CN112079633B discloses a nickel-zinc high magnetic permeability material with a wide temperature range and a low specific temperature coefficient and a preparation method thereof. The nickel-zinc high magnetic permeability material with a wide temperature range and a low specific temperature coefficient of the invention comprises a main component and an auxiliary component, wherein the main component, calculated by the total amount of Fe2O3, ZnO, NiO, and CuO, contains 47-49.8 mol% of Fe2O3, 11.6-15.6 mol% of NiO, and 30-34.5 mol% of ZnO, and the remainder is CuO; the content of the auxiliary component, calculated by the total weight of the main component, comprises 0.01-0.3 wt% of Co2O3, 0.05-0.25 wt% of SnO2, and 0.03-0.4 wt% of Bi2O3. The material has the advantages of high magnetic permeability and high Bs, but its sintering temperature is high, and the cost reduction effect cannot be achieved, and its Curie temperature is low, and it cannot be used as a magnetic bead inductor.

[0007] CN111056829A discloses a high-frequency, low-power ferrite. The high-frequency, low-power manganese-zinc ferrite material prepared by the formula and process of the present invention has a power consumption of only 150KW / m at 100°C under the test conditions of 1MHz and 50mT. 3 At the same time, it also has a higher sintering Bs, reaching 500mT (25℃) and 410mT (100℃), but the performance of this patent fails to meet the required requirements at higher frequencies. The paper of the University of Electronic Science and Technology of China introduces a high-frequency and low-power nickel-zinc ferrite for MHz frequency band. It uses NiZn iron-deficient formula and special additives, plus appropriate preparation process. The final material loss (3MHz, 10mT) is 203.6mW / cm 3 . However, the above technologies do not have higher frequency performance.

[0008] Therefore, how to prepare a high-frequency and low-power nickel-zinc ferrite material is an important research direction in this field. Summary of the invention

[0009] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a nickel-zinc ferrite material and its preparation method and application. A nickel-zinc ferrite material for high frequency, low power consumption and high Tc is prepared, which solves the problem of high frequency and low power consumption of the material at 4MHz to 14MHz, thereby improving the applicability of power magnetic products such as common-mode inductors, pulse transformers and laminated magnetic beads / inductors. This material can be better used in avionics, automotive electronics, communications electronics and other product industries.

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] One of the purposes of the present invention is to provide a nickel-zinc ferrite material, which comprises a main component and an auxiliary component. Taking the mass fraction of the nickel-zinc ferrite material as 100%, the main component comprises 65.8-67.8wt% Fe2O3, 6.8-7.5wt% NiO, 16.5-17wt% ZnO and 6.2-8.5wt% CuO, wherein the mass fraction of Fe2O3 can be 65.8wt%, 66wt%, 66.2wt%, 66.4wt%, 66.6wt%, 66.8wt%, 67wt%, 67.2wt%, 67.4wt%, 67.6wt% or 67.8 wt%, etc., the mass fraction of NiO can be 6.8wt%, 7wt%, 7.2wt%, 7.4wt% or 7.5wt%, etc., the mass fraction of ZnO can be 16.5wt%, 16.8wt% or 17.0wt%, etc., the mass fraction of CuO can be 6.2wt%, 6.4wt%, 6.6wt%, 6.8wt%, 7.0wt%, 7.2wt%, 7.4wt%, 7.6wt%, 7.8wt%, 8.0wt%, 8.2wt%, 8.4wt%, 8.5wt%, etc., but are not limited to the listed values, and other values ​​not listed within the above numerical ranges are equally applicable.

[0012] The auxiliary costs include Bi2O3, MgO and nano-SiO2.

[0013] In the present invention, the mass fraction of Fe2O3 is controlled between 65.8 and 67.8wt%, the mass fraction of NiO is controlled between 6.8 and 7.5wt%, the mass fraction of ZnO is controlled between 16.5 and 17wt% and the mass fraction of CuO is controlled between 6.2 and 8.5wt%. The present invention achieves a higher magnetic permeability value and a higher Tc under a wide temperature range by controlling the contents of Fe2O3, NiO, ZnO and CuO. When the content of Fe2O3 exceeds the range of 65.8 to 67.8wt%, the magnetic permeability will decrease. When the mass fraction of NiO exceeds the range of 6.8 to 7.5wt%, the high-frequency loss performance will deteriorate. When the mass fraction of ZnO exceeds the range of 16.5 to 17wt%, the saturation magnetic induction intensity of the material will be reduced, thereby reducing the use frequency of the material. When the content of CuO exceeds the range of 6.2 to 8.5wt%, the magnetic permeability will decrease and the high-frequency loss will increase.

[0014] The present invention adds Bi2O3 to reduce the sintering temperature, adds SiO2, and provides Si 4+ , nano Bi 3+ and Si 4+ Uniform grain boundaries can be formed, thereby taking into account the low power consumption performance of 1MHz and 20MHz. MgO and Bi2O3 of the present invention form Bi-Mg bonds. When Bi-Mg and NiZn ferrite undergo solid phase reaction, they mainly grow on the grain boundaries, thereby improving the insulation impedance performance and reducing high-frequency loss.

[0015] As a preferred technical solution of the present invention, taking the mass fraction of the nickel-zinc ferrite material as 100%, the auxiliary components include 0.6-3wt% Bi2O3, 1.5-2.5wt% MgO and 0.03-0.05wt% nano-SiO2, wherein the mass fraction of the Bi2O3 can be 0.6wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt% or 3wt%, etc., wherein the mass fraction of the MgO can be 1.5wt%, 2.0wt% or 2.5wt%, etc., wherein the mass fraction of the nano-SiO2 can be 0.03wt%, 0.04wt% or 0.05wt%, etc., but are not limited to the listed values, and other unlisted values ​​within the above numerical ranges are equally applicable.

[0016] In the present invention, if the mass fraction of Bi2O3 exceeds 3wt%, it will cause crystallization on the surface of the magnet, which will increase the power consumption Pcv value. If the mass fraction of Bi2O3 is too small, it will not play a role in assisting sintering.

[0017] In the present invention, if the mass fraction of MgO is too large, the magnetic permeability will be low, and if the mass fraction of MgO is too small, the triple boundary cannot be formed and the high-frequency loss will increase.

[0018] In the present invention, if the mass fraction of nano-SiO2 is too large, the magnet crystals will be too large. If the mass fraction of nano-SiO2 is too small, there will be no sintering effect, the grains will grow smaller, the sintering density will be lower, the material magnetic permeability will be low, and the high-frequency loss requirements will not be met.

[0019] A second object of the present invention is to provide a method for preparing the nickel-zinc ferrite material as described in the first object, the preparation method comprising:

[0020] The raw materials of the nickel-zinc ferrite material are mixed, and then first ball milling, pre-sintering, second ball milling, granulation molding and sintering are performed in sequence to obtain the nickel-zinc ferrite material.

[0021] The purpose of the first ball milling in the present invention is to mix the raw materials of nickel-zinc-ferrite extract, the purpose of pre-sintering is initial crystallization, the purpose of the second ball milling is to grind the powder into fine powder, granulate and shape the product with the required structure, sinter and grow spinel, and obtain a high-performance and low-loss magnet.

[0022] As a preferred technical solution of the present invention, the raw materials of the nickel-zinc ferrite material include an iron source, a nickel source, a zinc source, a copper source, a bismuth source, a magnesium source and a silicon source.

[0023] Preferably, the iron source comprises any one of iron oxide, iron nitrate, iron oxalate or iron phosphate, or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of iron oxide and iron nitrate, a combination of iron nitrate and iron oxalate, a combination of iron oxalate and iron phosphate, or a combination of iron oxide and iron phosphate, etc.

[0024] Preferably, the nickel source comprises any one of nickel oxide, nickel nitrate, nickel sulfate, nickel hydroxide or nickel phosphate, or a combination of at least two thereof, wherein typical but non-limiting examples of the combination include: a combination of nickel oxide and nickel nitrate, a combination of nickel nitrate and nickel sulfate, a combination of nickel sulfate and nickel hydroxide, or a combination of nickel hydroxide and nickel phosphate, etc.

[0025] Preferably, the zinc source comprises any one of zinc oxide, zinc nitrate, zinc sulfate or zinc phosphate, or a combination of at least two thereof, wherein typical but non-limiting examples of the combination include: a combination of zinc oxide and zinc nitrate, a combination of zinc nitrate and zinc sulfate, a combination of zinc sulfate and zinc phosphate, or a combination of zinc nitrate and zinc phosphate, etc.

[0026] Preferably, the copper source comprises any one of copper oxide, copper nitrate or copper sulfate, or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of copper oxide and copper nitrate, a combination of copper nitrate and copper sulfate, or a combination of copper oxide and copper sulfate, etc.

[0027] Preferably, the bismuth source includes any one of bismuth oxide, bismuth hydroxide, bismuth sulfide or bismuth nitrate, or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of bismuth oxide and bismuth hydroxide, a combination of bismuth hydroxide and bismuth sulfide, or a combination of bismuth sulfide and bismuth nitrate, etc.

[0028] Preferably, the magnesium source includes any one of magnesium oxide, talc or magnesium hydroxide, or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of magnesium oxide and talc, a combination of talc and magnesium hydroxide, or a combination of magnesium oxide and magnesium hydroxide.

[0029] Preferably, the silicon source comprises any one of nano-silicon oxide, silicic acid or water glass, or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of nano-silicon oxide and silicic acid, a combination of silicic acid and water glass, or a combination of nano-silicon oxide and water glass, etc.

[0030] As a preferred technical solution of the present invention, in the first ball mill, the mass ratio of the raw material of nickel zinc ferrite, the ball milling medium and water is 1:(4-8):(0.5-1.2), wherein the mass ratio can be 1:4:0.5, 1:4:0.8, 1:4:1.2, 1:5:0.5, 1:5:0.8, 1:5:1.2, 1:6:0.5, 1:6:0.8, 1:6:1.2, 1:7:0.5, 1:7:0.8, 1:7:1.2, 1:8:0.5, 1:8:0.8 or 1:8:1.2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the first ball milling time is 20 to 60 min, wherein the time can be 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, spray granulation is performed after the first ball milling.

[0033] As a preferred technical solution of the present invention, the pre-calcination temperature is 780-950°C, wherein the temperature can be 780°C, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 920°C, 940°C or 950°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] If the pre-firing temperature in the present invention is too high, the secondary grinding particle size is difficult to achieve, which will cause disadvantages in subsequent sintering. If the pre-firing temperature is too low, uniform crystallized material cannot be obtained, and subsequent sintering will also be abnormal.

[0035] Preferably, the pre-burning time is 2 to 4 hours, wherein the time may be 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In the present invention, if the pre-firing time is too long, the final sintering temperature will be too high, which will also cause unfavorable sintering. If the pre-firing time is too short, the actual sintering temperature will be low and the spinel body cannot be obtained.

[0037] As a preferred technical solution of the present invention, the pre-burned powder is obtained after the pre-burning, and the pre-burned powder is subjected to a second ball milling.

[0038] Preferably, in the second ball milling, water, a binder, a dispersant and a defoaming agent are added to the pre-calcined powder.

[0039] Preferably, the adhesive comprises any one of polyvinyl alcohol, polyvinyl butyral, hydroxy cellulose or polyacrylate, or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of polyvinyl alcohol and polyvinyl butyral, a combination of polyvinyl butyral and hydroxy cellulose or polyacrylate, or a combination of polyvinyl alcohol and polyacrylate, etc.

[0040] Preferably, the dispersant comprises any one of amine citrate, sodium stearate, polyacrylic acid or triethanolamine, or a combination of at least two thereof, wherein typical but non-limiting examples of the combination include: a combination of amine citrate and sodium stearate, a combination of sodium stearate and polyacrylic acid, or a combination of polyacrylic acid and triethanolamine, etc.

[0041] Preferably, the defoaming agent comprises any one of n-octanol, tributyl phosphate, stearic acid or polyethylene glycol, or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of n-octanol and tributyl phosphate, a combination of tributyl phosphate and stearic acid, a combination of stearic acid and polyethylene glycol, or a combination of n-octanol and polyethylene glycol, etc.

[0042] Preferably, the mass ratio of the pre-burned powder, water, binder, dispersant and defoamer is 100:(40-150):(4-20):(0.1-2):(0.001-0.0025, wherein the mass ratio can be 100:40:4:0.1:0.001, 100:40:10:1:0.002, 100:40:20:2:0.0025, 100:60:8:0.5:0.0015, 100:70: 15:1.5:0.002, 100:90:12:2:0.001, 100:100:20:0.1:0.0025, 100:120:4:2:0.001, 100:130:20:0.1:0.0025, 100:140:15:0.1:0.001 or 100:150:20:2:0.0025, etc., but are not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0043] In the present invention, the mass fractions of the pre-burned powder, water, adhesive, dispersant and defoamer exceed 100:(40-150):(4-20):(0.1-2):(0.001-0.0025), the slurry will be thicker, the spray granulation will not be smooth, and the feed pipe will be blocked. The binder is added to facilitate the granular material to form balls, the dispersant is used to prevent the powder from agglomerating, and the defoamer is used to ball mill with glue, which will generate bubbles and allow the defoamer to remove bubbles.

[0044] Preferably, the second ball milling includes low-speed milling and high-speed milling performed sequentially.

[0045] Preferably, the rate of the low-speed grinding is 20 to 60 rpm, wherein the rate may be 20 rpm, 25 rpm, 30 rpm, 35 rpm, 40 rpm, 45 rpm, 50 rpm, 55 rpm or 60 rpm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] Preferably, the low-speed grinding time is 2 to 10 min, wherein the time can be 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] Preferably, the high-speed grinding rate is 300-360 rpm, wherein the rate may be 300 rpm, 310 rpm, 320 rpm, 330 rpm, 340 rpm, 350 rpm or 360 rpm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the high-speed grinding time is 0.5 to 2 hours, wherein the time may be 0.5 hours, 0.8 hours, 1.0 hours, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours or 2 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] As a preferred technical solution of the present invention, the granulation molding includes spray granulation.

[0050] Preferably, after the granulation molding, a product with a particle size of 30 to 200 μm is obtained, wherein the particle size of the product can be 30 μm, 50 μm, 70 μm, 90 μm, 110 μm, 130 μm, 150 μm, 170 μm, 190 μm or 200 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] Preferably, the sintering includes a first stage of temperature increasing sintering, a second stage of temperature increasing sintering, a first stage of temperature decreasing sintering and a second stage of temperature decreasing sintering performed in sequence.

[0052] The purpose of selecting two-stage heating sintering and two-stage cooling sintering in the present invention is to optimize the sintering performance of the product. The two-stage heating sintering is to make the sample debinding normal, the product porosity low and the density good. The two-stage cooling sintering is to make the product no longer undergo reduction reaction, so that the high-frequency performance of the sample meets the requirements.

[0053] Preferably, the heating rate of the one-stage temperature rising sintering is 0.5-2.5°C / min, wherein the heating rate can be 0.5°C / min, 0.8°C / min, 1.0°C / min, 1.2°C / min, 1.4°C / min, 1.6°C / min, 1.8°C / min, 2.0°C / min, 2.2°C / min, 2.4°C / min or 2.5°C / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In the present invention, if the heating rate of the one-stage heating sintering is too high, the debinding and degassing will not be smooth, which will cause the sample to crack. If the heating rate of the one-stage heating sintering is too low, the cost will be greatly increased.

[0055] Preferably, the temperature of the first stage of heating sintering is 550-750°C, wherein the temperature may be 550°C, 600°C, 650°C, 700°C or 750°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] If the temperature of the first stage sintering is too high, it will be unfavorable for the growth of grains and thus cause large high-frequency losses. If the temperature of the first stage sintering is too low, the glue is not completely discharged, resulting in more holes inside the crystal.

[0057] Preferably, the holding time of the one-stage temperature rising sintering is 2 to 7 hours, wherein the time can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours or 7 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] Preferably, the heating rate of the two-stage temperature rising sintering is 1-3°C / min, wherein the heating rate can be 1°C / min, 2°C / min or 3°C / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] If the heating rate of the two-stage sintering is too high, the grains will grow too large, and the loss performance will not meet the requirements. If the heating rate of the two-stage sintering is too low, the grains will grow too small, resulting in low magnetic permeability and large high-frequency loss.

[0060] Preferably, the temperature of the second-stage heating sintering is 880-1150°C, wherein the temperature can be 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 1000°C, 1050°C, 1100°C or 1150°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] If the temperature of the second-stage sintering is too high, the grains will grow too large and the loss will be poor. If the temperature of the second-stage sintering is too low, the product will not be well-fired, the material density will not be reached, and the loss performance will also be poor.

[0062] Preferably, the holding time of the two-stage temperature rising sintering is 2 to 5 hours, wherein the holding time can be 2 hours, 3 hours, 4 hours or 5 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] Preferably, the cooling rate of the one-stage cooling sintering is 4 to 7°C / min, wherein the cooling rate can be 4°C / min, 5°C / min, 6°C / min or 7°C / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] Preferably, the temperature of the first stage cooling sintering is 550-650°C, wherein the temperature can be 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C or 650°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] Preferably, the atmosphere of the first stage of temperature reduction sintering is an air atmosphere.

[0066] Preferably, the cooling rate of the two-stage cooling sintering is 6 to 10°C / min, wherein the cooling rate can be 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] Preferably, the temperature of the second-stage cooling sintering is 25-75°C, wherein the temperature can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C or 75°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] Preferably, the atmosphere of the second-stage temperature reduction sintering is an air atmosphere.

[0069] As a preferred technical solution of the present invention, the preparation method comprises:

[0070] After mixing the raw materials of the nickel-zinc ferrite material, first ball milling for 20 to 60 minutes, pre-calcining at a temperature of 780 to 950° C. for 2 to 4 hours, second ball milling, granulation, molding and sintering are sequentially performed to obtain the nickel-zinc ferrite material;

[0071] The second ball milling includes a low-speed ball milling time of 2 to 7 minutes and a high-speed ball milling time of 0.5 to 2 hours;

[0072] The sintering includes a first stage of temperature rising sintering, a second stage of temperature rising sintering, a first stage of temperature falling sintering and a second stage of temperature falling sintering in sequence. The heating rate of the first stage of temperature rising sintering is 0.5-2.5°C / min, the temperature is 550-750°C and the insulation time is 2-7h. The heating rate of the second stage of temperature rising sintering is 1-3°C / min, the temperature is 950-1150°C and the insulation time is 2-5h. The cooling rate of the first stage of temperature falling is 4-7°C / min, the temperature is 550-650°C, and the cooling rate of the second stage of temperature falling sintering is 6-10°C / min, and the temperature is 25-75°C.

[0073] The third object of the present invention is to provide an application of the nickel-zinc ferrite material as described in the first object, wherein the nickel-zinc ferrite material is applied in the field of soft magnetic ferrite technology.

[0074] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0075] Compared with the prior art, the present invention has the following beneficial effects:

[0076] The nickel-zinc ferrite material in the present invention has the excellent performance of high frequency, low power consumption and high Tc, which solves the problem of high loss of the nickel-zinc ferrite material under high frequency conditions, thereby improving the output stability applicability of the inductor at high frequency, and can be applied in the fields of avionics, automotive electronics and communication electronics. DETAILED DESCRIPTION

[0077] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0078] Example 1

[0079] The present embodiment provides a nickel-zinc ferrite material, which includes, by mass fraction, 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2.

[0080] This embodiment also provides a method for preparing the above nickel-zinc ferrite material, the preparation method comprising:

[0081] The raw materials of the nickel-zinc ferrite material are mixed and then subjected to first ball milling, pre-sintering, second ball milling, granulation, molding and sintering in sequence to obtain the nickel-zinc ferrite material.

[0082] The specific steps include:

[0083] (1) Ingredients: The raw materials of nickel-zinc ferrite include 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2. After weighing, deionized water is added to a ball mill for the first ball milling to achieve mixing and crushing, wherein the material: grinding medium: water ratio is 1:6:1, the first ball milling lasts for 40 minutes, and spray granulation is performed after the slurry is obtained;

[0084] (2) Pre-burning: Place the spray granulated material into a rotary kiln at a kiln temperature of 890±20°C and a feed rate of 150kg / hour for pre-burning for 3 hours;

[0085] (3) Second ball milling: the powder obtained after pre-calcination is placed in a ball mill, and then water, polyvinyl alcohol, ammonium citrate, n-octanol and pure water are added in appropriate amounts, wherein the ratio of pre-calcined material: water: polyvinyl alcohol, ammonium citrate and n-octanol is 100:60:10:1:0.0015. When performing the second ball milling, a low speed grinding of 20 to 60 rpm is first used (10 min), and then a high speed ball milling of 300 to 360 rpm is used for 1 hour;

[0086] (4) Granulation: The product after the second ball milling was transferred to a spray tower for spray granulation into 100 μm particles. The particles of this embodiment were shaped into a density of 3.1 g / cm 3 H25*15*10mm standard sample ring blank;

[0087] (5) sintering: sintering the granulated product to obtain the nickel-zinc ferrite material;

[0088] The sintering curve is as follows: one-stage heating sintering: heating rate of 2.5℃ / min in air, from room temperature to 650℃, keeping temperature for 5h;

[0089] Second stage heating sintering: heating rate is 1.3℃ / min to 920℃, and heat preservation is carried out for 3h;

[0090] One-stage cooling sintering: cooling to 600℃ in air atmosphere, cooling rate is 4.3℃ / min;

[0091] Second stage cooling sintering: cooling to 50℃ in air atmosphere, cooling rate is 6℃ / min.

[0092] Example 2

[0093] The present embodiment provides a nickel-zinc ferrite material, which includes, by mass fraction, 66.6wt% Fe2O3, 7.17wt% NiO, 16.6wt% ZnO, 6.28wt% CuO, 1.7wt% Bi2O3, 1.6wt% MgO and 0.05wt% nano-SiO2.

[0094] This embodiment also provides a method for preparing the above nickel-zinc ferrite material, the preparation method comprising:

[0095] The raw materials of the nickel-zinc ferrite material are mixed and then subjected to first ball milling, pre-sintering, second ball milling, granulation, molding and sintering in sequence to obtain the nickel-zinc ferrite material.

[0096] The specific steps include:

[0097] (1) Ingredients: The raw materials of nickel-zinc ferrite include 66.6wt% Fe2O3, 7.17wt% NiO, 16.6wt% ZnO, 6.28wt% CuO, 1.6wt% Bi2O3, 1.7wt% MgO and 0.05wt% nano-SiO2. After weighing, deionized water is added to a ball mill for the first ball milling to achieve mixing and crushing, wherein the material: grinding medium: water ratio is 1:6.5:0.5, the first ball milling lasts for 40 minutes, and spray granulation is performed after the slurry is obtained;

[0098] (2) Pre-burning: Place the spray granulated material into a rotary kiln at a kiln temperature of 890±20°C and a feed rate of 150kg / hour for pre-burning for 2h;

[0099] (3) Second ball milling: the powder obtained after pre-sintering is placed in a ball mill, and then appropriate amounts of water, polyvinyl butyral, sodium stearate, polypropylene and pure water are added, wherein the ratio of pre-sintered material: water: polyvinyl butyral: tributyl phosphate: stearic acid is 100:60:10:0.6:0.001. When performing the second ball milling, a low speed of 60 rpm is first used for grinding (10 min), and then a high speed ball milling time of 360 rpm is used for 2 hours;

[0100] (4) Granulation: The product after the second ball milling is transferred to a spray tower for spray granulation into 30 μm particles. The particles of this example are shaped into a particle size with a density of 3.25 g / cm 3 H25*15*10mm standard sample ring blank;

[0101] (5) sintering: sintering the granulated product to obtain the nickel-zinc ferrite material;

[0102] The sintering curve is as follows: one-stage heating sintering: heating rate of 2.5℃ / min in air, from room temperature to 650℃, keeping temperature for 4h;

[0103] Second stage heating sintering: heating rate is 1.3℃ / min to 1000℃, and heat preservation is carried out for 2.5h;

[0104] One-stage cooling sintering: cooling to 600℃ in air atmosphere, cooling rate is 6℃ / min;

[0105] Second stage cooling sintering: cooling to 50℃ in air atmosphere, cooling rate is 7℃ / min.

[0106] Example 3

[0107] The present embodiment provides a nickel-zinc ferrite material, which includes, by mass fraction, 67wt% Fe2O3, 7.5wt% NiO, 16.82wt% ZnO, 6.2wt% CuO, 0.6wt% Bi2O3, 1.85wt% MgO and 0.03wt% nano-SiO2.

[0108] This embodiment also provides a method for preparing the above nickel-zinc ferrite material, the preparation method comprising:

[0109] The raw materials of the nickel-zinc ferrite material are mixed and then subjected to first ball milling, pre-sintering, second ball milling, granulation, molding and sintering in sequence to obtain the nickel-zinc ferrite material.

[0110] The specific steps include:

[0111] (1) Ingredients: The raw materials of nickel-zinc ferrite include 67wt% Fe2O3, 7.5wt% NiO, 16.82wt% ZnO, 6.2wt% CuO, 0.6wt% Bi2O3, 1.85wt% MgO and 0.03wt% nano-SiO2, which are weighed and added with deionized water in a ball mill for the first ball milling to achieve mixing and crushing, wherein the material: grinding medium: water ratio is 1:5:0.8, the first ball milling takes 40 minutes, and the slurry is sprayed and granulated;

[0112] (2) Pre-burning: Place the spray granulated material into a rotary kiln at a kiln temperature of 890±20°C and a feed rate of 150kg / hour for pre-burning for 4 hours;

[0113] (3) Second ball milling: the powder obtained after pre-calcination is placed in a ball mill, and then appropriate amounts of water, hydroxycellulose, polyacrylic acid, stearic acid and pure water are added, wherein the ratio of pre-calcined material: water: hydroxycellulose: polyacrylic acid: stearic acid is 100:60:12:1.2:0.002. When performing the second ball milling, a low speed of 20 rpm is first used for grinding (10 min), and then a high speed ball milling time of 300 rpm is used for 2 hours;

[0114] (4) Granulation: The product after the second ball milling is transferred to a spray tower for spray granulation into 200 μm particles. The particles of this example are shaped into a particle size of 3.00 g / cm 3 H25*15*10mm standard sample ring blank;

[0115] (5) sintering: sintering the granulated product to obtain the nickel-zinc ferrite material;

[0116] The sintering curve is as follows: one-stage heating sintering: heating rate 2℃ / min in air, from room temperature to 750℃, keeping temperature for 5h;

[0117] Second stage heating sintering: heating rate is 3℃ / min to 930℃, and keeping temperature for 5h;

[0118] One-stage cooling sintering: cooling to 600℃ in air atmosphere, cooling rate is 4℃ / min;

[0119] Second stage cooling sintering: cooling to 50℃ in air atmosphere, cooling rate is 6.5℃ / min.

[0120] Example 4

[0121] The present embodiment provides a nickel-zinc ferrite material, which includes, by mass fraction, 67.1wt% Fe2O3, 6.8wt% NiO, 16.52wt% ZnO, 6.35wt% CuO, 1.2wt% Bi2O3, 2wt% MgO and 0.03wt% nano-SiO2.

[0122] This embodiment also provides a method for preparing the above nickel-zinc ferrite material, the preparation method comprising:

[0123] The raw materials of the nickel-zinc ferrite material are mixed and then subjected to first ball milling, pre-sintering, second ball milling, granulation, molding and sintering in sequence to obtain the nickel-zinc ferrite material.

[0124] The specific steps include:

[0125] (1) Ingredients: The raw materials of nickel-zinc ferrite include 67.1wt% Fe2O3, 6.8wt% NiO, 16.52wt% ZnO, 6.35wt% CuO, 1.2wt% Bi2O3, 2wt% MgO and 0.03wt% nano-SiO2, which are weighed and added with deionized water in a ball mill for the first ball milling to achieve mixing and crushing, wherein the material: grinding medium: water ratio is 1:3.5:0.6, the first ball milling takes 40 minutes, and the slurry is sprayed and granulated;

[0126] (2) Pre-burning: Place the spray granulated material into a rotary kiln at a kiln temperature of 890±20°C and a feed rate of 150kg / hour for pre-burning for 3 hours;

[0127] (3) Second ball milling: the powder obtained after pre-calcination is placed in a ball mill, and then appropriate amounts of water, polyacrylate, triethanolamine, polyethylene glycol and pure water are added, wherein the ratio of pre-calcined material: water: polyacrylate: triethanolamine: polyethylene glycol is 100:60:10:1:0.0015. When performing the second ball milling, a low speed grinding of 40 rpm is first adopted (3 min), and then a high speed ball milling of 330 rpm is adopted for 2 hours;

[0128] (4) Granulation: The product after the second ball milling is transferred to a spray tower for spray granulation into particles of 100 μm. The particles of this example are shaped into particles with a density of 3.15 g / cm 3 H25*15*10mm standard sample ring blank;

[0129] (5) sintering: sintering the granulated product to obtain the nickel-zinc ferrite material;

[0130] The sintering curve is as follows: one stage heating sintering: heating rate of 1.25℃ / min in air, from room temperature to 750℃, keeping temperature for 2h;

[0131] Second stage heating sintering: heating rate is 1.6℃ / min to 950℃, and heat preservation is carried out for 2.5h;

[0132] One-stage cooling sintering: cooling to 600℃ in air atmosphere, cooling rate is 4.7℃ / min;

[0133] Second stage cooling sintering: cooling to 50℃ in air atmosphere, cooling rate is 7℃ / min.

[0134] Example 5

[0135] The present embodiment provides a nickel-zinc ferrite material, which includes, by mass fraction, 66.45wt% Fe2O3, 6.8wt% NiO, 16.5wt% ZnO, 6.2wt% CuO, 1.8wt% Bi2O3, 2.2wt% MgO and 0.05wt% nano-SiO2.

[0136] This embodiment also provides a method for preparing the above nickel-zinc ferrite material, the preparation method comprising:

[0137] The raw materials of the nickel-zinc ferrite material are mixed and then subjected to first ball milling, pre-sintering, second ball milling, granulation, molding and sintering in sequence to obtain the nickel-zinc ferrite material.

[0138] The specific steps include:

[0139] (1) Ingredients: The raw materials of nickel-zinc ferrite include 66.45wt% Fe2O3, 6.8wt% NiO, 16.5wt% ZnO, 6.2wt% CuO, 1.8wt% Bi2O3, 2.2wt% MgO and 0.05wt% nano-SiO2, which are weighed and added with deionized water in a ball mill to perform the first ball milling to achieve mixing and crushing, wherein the material: grinding medium: water ratio is 1:6:1.1, the first ball milling takes 40 minutes, and spray granulation is performed after the slurry is obtained;

[0140] (2) Pre-burning: Place the spray granulated material into a rotary kiln at a kiln temperature of 890±20°C and a feed rate of 150kg / hour for pre-burning for 3 hours;

[0141] (3) Second ball milling: the powder obtained after pre-calcination is placed in a ball mill, and then water, polyvinyl alcohol, ammonium citrate, n-octanol and pure water are added in appropriate amounts, wherein the ratio of pre-calcined material: water: polyvinyl alcohol: ammonium citrate: n-octanol is 100:50:10:1:0.0025. When performing the second ball milling, a low speed grinding of 40 rpm is first adopted (10 min), and then a high speed ball milling of 330 rpm is adopted for 2 hours;

[0142] (4) Granulation: The product after the second ball milling is transferred to a spray tower for spray granulation into particles of 100 μm. The particles of this example are shaped into particles with a density of 3.15 g / cm 3 H25*15*10mm standard sample ring blank;

[0143] (5) sintering: sintering the granulated product to obtain the nickel-zinc ferrite material;

[0144] The sintering curve is as follows: one-stage heating sintering: heating rate of 0.55℃ / min in air, from room temperature to 550℃, keeping temperature for 7h;

[0145] Second stage heating sintering: heating rate is 1.2℃ / min to 880℃, and keeping temperature for 5h;

[0146] One-stage cooling sintering: cooling to 600℃ in air atmosphere, cooling rate is 5℃ / min;

[0147] Second stage cooling sintering: cooling to 50℃ in air atmosphere, cooling rate is 8℃ / min.

[0148] Example 6

[0149] The present embodiment provides a nickel-zinc ferrite material, which includes, by mass fraction, 67.66wt% Fe2O3, 6.8wt% NiO, 16.6wt% ZnO, 6.2wt% CuO, 1.2wt% Bi2O3, 1.5wt% MgO and 0.04wt% nano-SiO2.

[0150] This embodiment also provides a method for preparing the above nickel-zinc ferrite material, the preparation method comprising:

[0151] The raw materials of the nickel-zinc ferrite material are mixed and then subjected to first ball milling, pre-sintering, second ball milling, granulation, molding and sintering in sequence to obtain the nickel-zinc ferrite material.

[0152] The specific steps include:

[0153] (1) Ingredients: The raw materials of nickel-zinc ferrite include 67.66wt% Fe2O3, 6.8wt% NiO, 16.6wt% ZnO, 6.2wt% CuO, 1.2wt% Bi2O3, 1.5wt% MgO and 0.04wt% nano-SiO2, which are weighed and added with deionized water in a ball mill to perform the first ball milling to achieve mixing and crushing, wherein the material: grinding medium: water ratio is 1:5:1, the first ball milling lasts for 30 minutes, and spray granulation is performed after the slurry is obtained;

[0154] (2) Pre-burning: Place the spray granulated material into a rotary kiln at a kiln temperature of 910±20°C and a feed rate of 150kg / hour for pre-burning for 3h;

[0155] (3) Second ball milling: the powder obtained after pre-calcination is placed in a ball mill, and then appropriate set values ​​of water, polyvinyl butyral, sodium stearate, n-octanol and pure water are added, wherein the ratio of pre-calcined material: water: polyvinyl butyral: sodium stearate: n-octanol is 100:60:10:1:0.01. When performing the second ball milling, a low speed grinding of 40 rpm is first adopted (10 min), and then a high speed ball milling of 330 rpm is used for 1.2 hours;

[0156] (4) Granulation: The product after the second ball milling is transferred to a spray tower for spray granulation into particles of 100 μm. The particles of this example are shaped into particles with a density of 3.15 g / cm 3 H25*15*10mm standard sample ring blank;

[0157] (5) sintering: sintering the granulated product to obtain the nickel-zinc ferrite material;

[0158] The sintering curve is as follows: one-stage heating sintering: heating rate of 1.5℃ / min in air, from room temperature to 600℃, keeping temperature for 3h;

[0159] Second stage heating sintering: heating rate is 1.5℃ / min to 980℃, and keeping temperature for 3h;

[0160] One-stage cooling sintering: cooling to 600℃ in air atmosphere, cooling rate is 5.7℃ / min;

[0161] Second stage cooling sintering: cooling to 50℃ in air atmosphere, cooling rate is 6℃ / min.

[0162] Example 7

[0163] In this embodiment, except that 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2 are replaced by 66.2wt% Fe2O3, 6.8wt% NiO, 16.56wt% ZnO, 6.21wt% CuO, 3wt% Bi2O3, 1.2wt% MgO and 0.03wt% nano-SiO2, other conditions are the same as those in Example 1.

[0164] Example 8

[0165] In this embodiment, except that 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2 are replaced by 66.42wt% Fe2O3, 6.6wt% NiO, 16.5wt% ZnO, 6.2wt% CuO, 2.0wt% Bi2O3, 2.245wt% MgO and 0.035wt% nano-SiO2, other conditions are the same as those in Example 1.

[0166] Example 9

[0167] In this embodiment, except that 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2 are replaced by 65.51wt% Fe2O3, 7wt% NiO, 16.8wt% ZnO, 6.25wt% CuO, 2.4wt% Bi2O3, 2wt% MgO and 0.04wt% nano-SiO2, other conditions are the same as those in Example 1.

[0168] Example 10

[0169] In this embodiment, except that 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2 are replaced by 65.8wt% Fe2O3, 6.85wt% NiO, 16wt% ZnO, 6.35wt% CuO, 3.2wt% Bi2O3, 1.75wt% MgO and 0.05wt% nano-SiO2, other conditions are the same as those in Example 1.

[0170] Embodiment 11

[0171] In this embodiment, except that 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2 are replaced by 65.5wt% Fe2O3, 7wt% NiO, 17wt% ZnO, 9wt% CuO, 0.5wt% Bi2O3, 0.99wt% MgO and 0.01wt% nano-SiO2, other conditions are the same as those in Example 1.

[0172] Example 12

[0173] In this embodiment, except that 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2 are replaced by 66.2wt% Fe2O3, 7wt% NiO, 16wt% ZnO, 5.39wt% CuO, 2.4wt% Bi2O3, 3wt% MgO and 0.01wt% nano-SiO2, other conditions are the same as those in Example 1.

[0174] Embodiment 13

[0175] In this embodiment, the conditions are the same as those in embodiment 1 except that the two-stage temperature increase sintering is replaced by heating in air at a heating rate of 2.5°C / min from room temperature to 920°C and keeping the temperature for 8 hours.

[0176] Comparative Example 1

[0177] In this comparative example, except that 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2 are replaced by 67.9wt% Fe2O3, 5.5wt% NiO, 16wt% ZnO, 6.66wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.04wt% nano-SiO2, other conditions are the same as those in Example 1.

[0178] Comparative Example 2

[0179] In this comparative example, except that 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2 are replaced by 67wt% Fe2O3, 7.6wt% NiO, 16.1wt% ZnO, 4.15wt% CuO, 2.7wt% Bi2O3, 2.4wt% MgO and 0.05wt% nano-SiO2, other conditions are the same as those in Example 1.

[0180] Comparative Example 3

[0181] In this comparative example, except that 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2 are replaced by 65.8wt% Fe2O3, 7.34wt% NiO, 17.16% ZnO, 4.665wt% CuO, 2.8wt% Bi2O3, 2.2wt% MgO and 0.035wt% nano-SiO2, other conditions are the same as those in Example 1.

[0182] Comparative Example 4

[0183] In this comparative example, except that 65.8wt% Fe2O3, 7.07wt% NiO, 16.5wt% ZnO, 6.7wt% CuO, 2.4wt% Bi2O3, 1.5wt% MgO and 0.03wt% nano-SiO2 are replaced by 65.8wt% Fe2O3, 6.8wt% NiO, 16.5wt% ZnO, 8.55wt% CuO, 1.605wt% Bi2O3, 0.71wt% MgO and 0.035wt% nano-SiO2, other conditions are the same as those in Example 1.

[0184] Comparative Example 5

[0185] Except for not adding Fe2O3, other conditions in this comparative example are the same as those in Example 1.

[0186] Comparative Example 6

[0187] Except that NiO is not added, other conditions in this comparative example are the same as those in Example 1.

[0188] Comparative Example 7

[0189] Except that ZnO is not added, other conditions in this comparative example are the same as those in Example 1.

[0190] Comparative Example 8

[0191] Except that CuO is not added, other conditions in this comparative example are the same as those in Example 1.

[0192] Comparative Example 9

[0193] Except for not adding Bi2O3, other conditions in this comparative example are the same as those in Example 1.

[0194] Comparative Example 10

[0195] Except that MgO is not added, other conditions in this comparative example are the same as those in Example 1.

[0196] Comparative Example 11

[0197] Except that Bi2O3, MgO and nano-SiO2 are not added, other conditions in this comparative example are the same as those in Example 1.

[0198] Comparative Example 12

[0199] In this comparative example, except that the first ball milling process is not performed and pre-sintering is performed directly, other conditions are the same as those in Example 1.

[0200] Comparative Example 13

[0201] Except that the pre-firing process is not performed, other conditions in this comparative example are the same as those in Example 1.

[0202] The nickel-zinc ferrite materials prepared in Examples 1-13 and Comparative Examples 1-13 were subjected to inductance, magnetic permeability and power consumption tests, and the test results are shown in Table 1.

[0203] The test method is as follows: use Agilent E4991 to test the inductance of a ring of nickel-zinc ferrite material with an outer diameter of 25mm, an inner diameter of 15mm, and a height of 10mm, and then calculate the magnetic permeability μi based on the size factor; use an LCR magnetic material tester and a high and low temperature controllable oven to test the Curie temperature Tc and the magnetic permeability at various frequencies; use the Yanqi BH8218 instrument to test the power consumption Pcv (13.56MHz, 5mT).

[0204] Table 1

[0205]

[0206]

[0207] From the above table, we can see that bismuth oxide has a sintering effect, which can make the magnet denser, MgO has a grain refinement effect, resulting in low high-frequency loss, and trace silicon oxide also has a sintering effect, which can increase the density of the magnet and thus improve the high-frequency characteristics of the magnet.

[0208] The NiO content in the main formula of Example 8 is relatively low, and although its magnetic permeability and high-frequency loss values ​​will not differ too much, its Curie temperature is relatively low; the Fe2O3 in Example 9 is relatively low, resulting in a significant decrease in magnetic permeability, an increase in high-frequency loss, and a decrease in its Curie temperature due to the reduced Fe-O-Fe effect; the additive Bi2O3 in Example 10 is large, resulting in a significant growth of the sintered magnet grains, an increase in the loss value of the crystal, and a decrease in its high-frequency magnetic permeability; the main components of Example 11 are all within the range, but a small amount of nano-SiO2 is added, and although the magnetic permeability is within the normal range, its loss value will be relatively large; a small amount of CuO in Example 12 will not only increase the sintering temperature, but also cause the magnetic permeability to be relatively low, and thus the high-frequency loss performance is poor. In Example 13, the two-stage temperature rise sintering is replaced by a single-stage temperature rise sintering, and the inductance, magnetic permeability test and power consumption test performance of the nickel-zinc ferrite material are all reduced.

[0209] In Comparative Examples 1-4, when the addition amounts of Fe2O3, NiO, ZnO and CuO exceed the range, the inductance, magnetic permeability test and power consumption test performances of the nickel-zinc ferrite material all decrease.

[0210] In Comparative Examples 5-8, when Fe2O3, NiO, ZnO or CuO is not added, the inductance, magnetic permeability test and power test performance of the nickel-zinc ferrite material are all reduced.

[0211] In Comparative Examples 9-11, without adding auxiliary components, the inductance, magnetic permeability test and power consumption test performance of the nickel-zinc ferrite material all decreased.

[0212] In Comparative Example 12, the first ball milling was not performed, and pre-sintering was performed directly, and the inductance, magnetic permeability test and power consumption test performance of the nickel-zinc ferrite material all decreased.

[0213] In Comparative Example 13, without pre-burning, the inductance, magnetic permeability and power consumption test performances of the nickel-zinc ferrite material all decreased.

[0214] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A nickel-zinc ferrite material, characterized in that: The nickel-zinc ferrite material includes a main component and an auxiliary component. Taking the mass fraction of the nickel-zinc ferrite material as 100%, the main component includes 65.8-67.8wt% Fe2O3, 6.8-7.5wt% NiO, 16.5-17wt% ZnO and 6.2-8.5wt% CuO, and the auxiliary component includes Bi2O3, MgO and nano-SiO2.

2. The nickel-zinc ferrite material according to claim 1, characterized in that: Taking the mass fraction of the nickel-zinc ferrite material as 100%, the auxiliary components include 0.6-3wt% Bi2O3, 1.5-2.5wt% MgO and 0.03-0.05wt% nano-SiO2.

3. A method for preparing the nickel-zinc ferrite material according to claim 1 or 2, characterized in that: The preparation method comprises: The raw materials of the nickel-zinc ferrite material are mixed, and then first ball milling, pre-sintering, second ball milling, granulation molding and sintering are performed in sequence to obtain the nickel-zinc ferrite material.

4. The preparation method according to claim 3, characterized in that: The raw materials of the nickel-zinc ferrite material include an iron source, a nickel source, a zinc source, a copper source, a bismuth source, a magnesium source and a silicon source; Preferably, the iron source comprises any one of iron oxide, iron nitrate, iron oxalate or iron phosphate, or a combination of at least two thereof; Preferably, the nickel source includes any one of nickel oxide, nickel nitrate, nickel sulfate, nickel hydroxide or nickel phosphate, or a combination of at least two thereof; Preferably, the zinc source includes any one or a combination of at least two of zinc oxide, zinc nitrate, zinc sulfate or zinc phosphate; Preferably, the copper source includes any one or a combination of at least two of copper oxide, copper nitrate or copper sulfate; Preferably, the bismuth source includes any one of bismuth oxide, bismuth hydroxide, bismuth sulfide or bismuth nitrate, or a combination of at least two thereof; Preferably, the magnesium source comprises any one or a combination of at least two of magnesium oxide, talc or magnesium hydroxide; Preferably, the silicon source includes any one of nano silicon oxide, silicic acid or water glass, or a combination of at least two of them.

5. The preparation method according to claim 3 or 4, characterized in that: In the first ball milling, the mass ratio of the raw material of the nickel-zinc ferrite material, the ball milling medium and water is 1:(4-8):(0.5-1.2); Preferably, the first ball milling time is 20 to 60 minutes; Preferably, spray granulation is performed after the first ball milling.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The pre-burning temperature is 780-950°C; Preferably, the pre-burning time is 2 to 4 hours.

7. The preparation method according to any one of claims 3 to 6, characterized in that: After the pre-burning, a pre-burned powder is obtained, and the pre-burned powder is subjected to a second ball milling; Preferably, in the second ball milling, water, a binder, a dispersant and a defoamer are added to the pre-burned powder; Preferably, the adhesive comprises any one or a combination of at least two of polyvinyl alcohol, polyvinyl butyral, hydroxy cellulose or polyacrylate; Preferably, the dispersant includes any one or a combination of at least two of ammonium citrate, sodium stearate, polyacrylic acid or triethanolamine; Preferably, the defoaming agent comprises any one or a combination of at least two of n-octanol, tributyl phosphate, stearic acid or polyethylene glycol; Preferably, the mass ratio of the pre-burned powder, water, binder, dispersant and defoamer is 100:(40-150):(4-20):(0.1-2):(0.001-0.0025); Preferably, the second ball milling comprises low-speed milling and high-speed milling performed sequentially; Preferably, the low-speed grinding rate is 20 to 60 rpm; Preferably, the low-speed grinding time is 2 to 10 minutes; Preferably, the high-speed grinding rate is 300-360 rpm; Preferably, the high-speed grinding time is 0.5 to 2 hours.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The granulation forming includes spray granulation; Preferably, after the granulation, a product having a particle size of 30 to 200 μm is obtained; Preferably, the sintering includes a first stage of temperature rising sintering, a second stage of temperature rising sintering, a first stage of temperature falling sintering and a second stage of temperature falling sintering performed in sequence; Preferably, the heating rate of the one-stage heating sintering is 0.5-2.5°C / min; Preferably, the temperature of the first stage of sintering is 550-750°C; Preferably, the holding time of the heating sintering step is 2 to 7 hours; Preferably, the heating rate of the second-stage heating sintering is 1-3°C / min; Preferably, the temperature of the second stage sintering is 880-1150°C; Preferably, the holding time of the second stage heating sintering is 2 to 5 hours; Preferably, the cooling rate of the first stage cooling sintering is 4-7°C / min; Preferably, the temperature of the first stage of cooling sintering is 550-650°C; Preferably, the atmosphere of the first stage of temperature reduction sintering is air atmosphere; Preferably, the cooling rate of the two-stage cooling sintering is 6 to 10°C / min; Preferably, the temperature of the second stage cooling sintering is 25-75°C; Preferably, the atmosphere of the second-stage temperature reduction sintering is an air atmosphere.

9. The preparation method according to any one of claims 3 to 8, characterized in that: The preparation method comprises: After mixing the raw materials of the nickel-zinc ferrite material, first ball milling for 20 to 60 minutes, pre-calcining at a temperature of 780 to 950° C. for 2 to 4 hours, second ball milling, granulation, molding and sintering are sequentially performed to obtain the nickel-zinc ferrite material; The second ball milling includes a low-speed ball milling time of 2 to 7 minutes and a high-speed ball milling time of 0.5 to 2 hours; The sintering includes a first stage of temperature rising sintering, a second stage of temperature rising sintering, a first stage of temperature falling sintering and a second stage of temperature falling sintering in sequence. The heating rate of the first stage of temperature rising sintering is 0.5-2.5°C / min, the temperature is 550-750°C and the insulation time is 2-7h. The heating rate of the second stage of temperature rising sintering is 1-3°C / min, the temperature is 950-1150°C and the insulation time is 2-5h. The cooling rate of the first stage of temperature falling is 4-7°C / min, the temperature is 550-650°C, and the cooling rate of the second stage of temperature falling sintering is 6-10°C / min, and the temperature is 25-75°C.

10. An application of the nickel-zinc ferrite material as claimed in claim 1 or 2, characterized in that: The nickel-zinc ferrite material is applied in the technical field of soft ferrite.

Citation Information

Patent Citations

  • High-frequency low-power-consumption manganese-zinc ferrite material and preparation method thereof

    CN111056829A

  • A nickel-zinc high permeability material with a wide temperature range and low specific temperature coefficient and its preparation method

    CN112079633B

Cited By

  • High-strength low-loss nickel-zinc-copper ferrite material and preparation method thereof

    CN120903928A

  • High-quality-factor high-strength-toughness nickel-zinc ferrite and preparation method thereof

    CN121318425A